Analysis The Influence of Communication Competence, Emotional Intelligence, and Organizational Culture on Employee Performance at PT. Esa Wahana - Tandiyono, Tan Evan; Andriani, Yuanita Dwi (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Vision and Mission of PT. Esa Wahana is to realize the development of quality and competitive Human Resources. Researchers conduct research related to communication competence, emotional intelligence, and organizational culture on the performance of employees in PT. Esa Wahana. The population in this study was all employees of PT. Esa Wahana which has a total of 70 people. The number of samples used in this study was as many as 50 people. The sampling method that will be used is to use Disproportionate stratified sampling. The data analysis techniques used are Test t and Test F with IBM SPSS Statistics 20 tool. T-Test results in order for communication competence, emotional intelligence, and organizational culture Sig values. indicates a value of 0.000; 0,041; 0.000 of which < 0.05 has a significant effect on employee performance. The value of the coefficient of determination (R2) of 76.6% means that the variables of communication competence, emotional intelligence and organizational culture are able to contribute 76.6% to the performance of employees at PT. Esa Wahana in 2022 while the remaining 23.4% is explained by other factors.